Terpenoids and Its Commercial Utility from Neem: The Nature’s Own Pharmacy: A Review - Sathish Kumar, A.S.; Subhash Chandra Bose, Kotte; Pavan Kumar, K.V.T.S.; Raghavan, Shriram; Murali, P.M. (Asian Journal of Chemistry, 2014)
Plant derived bio products have become integral part of world health care system which not only include botanical drugs but also agro chemicals, cosmetics, nutraceuticals, flavors and fragrances and so on. The World Bank estimates that global trade in plant derived products will grow at average 10-12 % per year and will reach whooping USD 123 billion by 2020. Inevitably this brought attention to our sthala vriksha or sacred tree neem (Azadirachta indica) considered as store house of high value products with vast array of biological activities like insecticidal, spermicidal, anticancer, hypoglycemic, antiulcer, antiinflammatory, and many more. However due to inherent complexities in scalability which includes consistent supply chain and difficulty in synthesizing bioactive metabolites using established chemical routes and seasonal variation in bio-efficacy with change in plant chemistry, place, age etc. makes large scale production of most of them is impossible. Hence there is need for a paradigm shift in combining traditional approaches with more sophisticated biotechnological methods to produce these products in heterologous system, thereby enabling a consistent scale-up at a commercial level. This article reviews the terpenoids reported in neem so far, their proposed biosynthetic pathways and potential avenues for expressing them in microbial cell factories.